2017
DOI: 10.3791/55647
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of the Mouse Pancreas for Histological Analysis and Metabolic Profiling

Abstract: We have been investigating the pancreas specific transcription factor, 1a cre-recombinase; lox-stop-lox- Kristen rat sarcoma, glycine to aspartic acid at the 12 codon (Ptf1a;LSL-Kras) mouse strain as a model of human pancreatic cancer. The goal of our current studies is to identify novel metabolic biomarkers of pancreatic cancer progression. We have performed metabolic profiling of urine, feces, blood, and pancreas tissue extracts, as well as histological analyses of the pancreas to stage the cancer progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
(11 reference statements)
0
12
0
Order By: Relevance
“…D16-00100). Surgical procedures were carried out as previously described 22–27. All authors completed online and in-class animal training prior to animal work.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…D16-00100). Surgical procedures were carried out as previously described 22–27. All authors completed online and in-class animal training prior to animal work.…”
Section: Methodsmentioning
confidence: 99%
“…All dissections and intestinal histologies were performed as described previously 22–29. Details regarding the histological procedures can be found in online supplementary material.…”
Section: Methodsmentioning
confidence: 99%
“…According to the methodology proposed by Veite‐Schmahl et al (), with brief modifications, animals were sacrificed and dissected to identify the pancreas. Anatomically, the organ was separated in to 3 regions, head, right lobe, and left lobe.…”
Section: Methodsmentioning
confidence: 99%
“…All authors and personnel involved were required to complete online and in class animal training prior to any work involving animals. All dissections were conducted as previously described [ 23 ]. The procedure began by placing the mouse into the anesthesia chamber, a glass jar with an isoflurane soaked pad and lid, for approximately one minute until the mouse was unconscious.…”
Section: Methodsmentioning
confidence: 99%
“…It has been previously reported that more than 80% of the ducts are expected to be normal at approximately 2.25 months, 68% of the ducts are expected to be normal from age 4–5 months, and 18% of the ducts are expected to be normal for mice in the age range from 7–10 months [ 6 ]. Mice were dissected following the procedures previously described [ 23 ]. Briefly, mice were euthanized once the targeted age was reached, and pancreata were collected from each mouse by dissection and placed into formalin overnight at room temperature.…”
Section: Methodsmentioning
confidence: 99%